Municipal Solid Waste Thermal Analysis—Pyrolysis Kinetics and Decomposition Reactions - Ewa Syguła; Kacper Świechowski; Małgorzata Hejna; Ines Kunaszyk; Andrzej Białowiec (Energies, 2021)
In this study, 12 organic waste materials were subjected to TG/DTG thermogravimetric analysis and DSC calorimetric analysis. These analyses provided basic information about thermochemical transformations and degradation rates during organic waste pyrolysis. Organic waste materials were divided into six basic groups as follows: paper, cardboard, textiles, plastics, hygiene waste, and biodegradable waste. For each group, two waste materials were selected to be studied. Research materials were (i) paper (receipts, cotton wool); (ii) cardboard (cardboard, egg carton); (iii) textiles (cotton, leather); (iv) plastics (polyethylene (PET), polyurethane (PU)); (v) hygiene waste (diapers, leno); and (vi) biodegradable waste (chicken meat, potato peel). Waste materials were chosen to represent the most abundant waste that can be found in the municipal solid waste stream. Based on TG results, kinetic parameters according to the Coats–Redfern method were determined. The pyrolysis activation energy was the highest for cotton, 134.5 kJ × (mol∙K)−1, and the lowest for leather, 25.2 kJ × (mol∙K)−1. The DSC analysis showed that a number of transformations occurred during pyrolysis for each material. For each transformation, the normalized energy required for transformation, or released during transformation, was determined, and then summarized to present the energy balance. The study found that the energy balance was negative for only three waste materials—PET (−220.1 J × g−1), leather (−66.8 J × g−1), and chicken meat (−130.3 J × g−1)—whereas the highest positive balance value was found for potato peelings (367.8 J × g−1). The obtained results may be applied for the modelling of energy and mass balance of municipal solid waste pyrolysis.